Technology innovation in library: a bibliometric review - Margono, Hendro; Rasyid, Rizka Adristi; Setiyarini, Melina Dewi (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2024)
Technological innovation is changing libraries and how libraries operate. This study presents a bibliometric analysis to identify key patterns and trends in research on technological innovation in libraries, based on the publication of papers indexed in Web of Science from 2019 to 2023. A total of 433 documents from 342 sources were analyzed using Biblioshiny and VOSViewer software. The results show an increasing interest in this research domain, despite a negative annual publication growth rate of -32.33% in recent years. The IEEE Winter Conference on Computer Vision Applications and the IEEE Symposium on Security and Privacy were the most productive sources. "Library" was the most frequent keyword found in 6% of documents, along with terms such as "model", "performance", and "system", highlighting the focus on developing and evaluating technological systems for libraries.  The findings summarize the key topics, trends, and leading countries driving technology innovation research for libraries over the past five years. This bibliometric review provides insights to guide future research efforts in this area.